ANALISIS KESANTUNAN BERBAHASA INDONESIA DALAM TINDAK TUTUR MASYARAKAT SEKITAR BELAWAN BAHAGIA (LINGKUNGAN XIX) - Ruwina, Ruwina; Harahap, Rosmawati (Universitas Islam Sumatera Utara, 2023)
This study aims to describe the forms of Indonesian politeness in the speech acts of the people around Belawan Bahagia (environment XIX). This study uses the qualitative research method of Leech's theory in the data acquisition process. In collecting data, the researcher used the observing and tapping method accompanied by the proficient involved listening technique, the proficient free listening technique, and the note taking technique. The results of data analysis and discussion of Indonesian politeness research in the speech acts of the people around Belawan Bahagia (environment XIX), the researcher found 3 forms of speech acts, namely (1) 2 data of locutionary speech acts, (2) 1 data of perlocutionary speech acts, ( 3) illocutionary speech acts as much as 1 data. And found 6 politeness maxims, namely (1) 1 data maxim of wisdom, (2) 1 data maxim of acceptance, (3) 1 data maxim of generosity, (4) 1 data maxim of modesty, (5) 1 data maxim of conformity 1 data, and (6) the maxim of sympathy as much as 2 data. Locutionary speech acts and sympathy maxims are mostly found by researchers.